Analysis of the transcripts encoding for antigenic proteins of bovine gammaherpesvirus 4 - Romeo, Florencia (2020)
The major glycoproteins of bovine gammaherpesvirus 4 (BoHV-4) are gB, gH, gM, gL, and gp180 with gB, gH, and gp180 being the most glycosylated. These glycoproteins participate in cell binding while some act as neutralization targets. Glycosylation of these envelope proteins may be involved in virion protection against neutralization by antibodies. In infected cattle, BoHV-4 induces an immune response characterized by low neutralizing antibody levels or an absence of such antibodies. Therefore, virus seroneutralization in vitro cannot always be easily demonstrated. The aim of this study was to evaluate the neutralizing capacity of 2 Argentine BoHV-4 strains and to associate those findings with the gene expression profiles of the major envelope glycoproteins. Expression of genes coding for the envelope glycoproteins occurred earlier in cells infected with isolate 10/154 than in cells infected with strain 07/435, demonstrating a distinct difference between the strains. Differences in serological response can be attributed to differences in the expression of antigenic proteins or to post-translational modifications that mask neutralizing epitopes. Strain 07/435 induced significantly high titers of neutralizing antibodies in several animal species in addition to bovines. The most relevant serological differences were observed in adult animals. This is the first comprehensive analysis of the expression kinetics of genes coding for BoHV-4 glycoproteins in 2 Argentine strains (genotypes 1 and 2). The results further elucidate the BoHV-4 life cycle and may also help determine the genetic variability of the strains circulating in Argentina.